Developments in theoretical and applied mechanics. Proceedings of the Third Southeastern Conference on Theoretical and Applied Mechanics, sponsored by University of South Carolina, held in Columbia, S. Carolina, March 31-April 1, 1966 - Shaw, W. A. (Elsevier Ltd. : Pergamon Press, 1967)
Developments in Theoretical and Applied Mechanics, Volume 3 presents papers on the proceedings of the Third Southeastern Conference on Theoretical and Applied Mechanics held in Columbia, S. Carolina on March 31-April 1, 1966. The book covers papers in the areas of continuum mechanics, elasticity, plates and shells, applied mechanics, experimental mechanics, wave propagation, dynamics, vibrations, and fluid mechanics. Physical chemists and mechanical engineers will find the book invaluable.